A new genus of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae) - Liu, Xianwei; Zhang, Dingjie (Zootaxa, 2007)
In this paper, one new genus, three new species are described: Alloxiphidiopsis gen. n., Alloxiphidiopsis cyclolamina sp. n., Alloxiphidiopsis longicauda sp. n. and Alloxiphidiopsis ovalis sp. n. (Meconematini). Two new combinations are proposed: Alloxiphidiopsis emarginata (Tinkham, 1944) comb. n. and Alloxiphidiopsis irregularis (Bey-Bienko, 1962) comb. n. from Xiphidiopsis. A key to the species is given.